Insecticidal Activity of the Whole Grass Extract of Typha angustifolia and its Active Component against Solenopsis invicta - Zhixiang Zhang (Universidade Estadual de Feira de Santana, 2014)
In this study, the toxicity of whole grass Typha angustifolia L. extract was determined in vitro by a “water tube” method to investigate the bioactivity of T. angustifolia L. against micrergates of red imported fire ants. Results indicated that the ethanol extract exhibited toxicity against the micrergates of red imported fire ants. Mortality was 100% after the micrergates were treated with 2000 mg/mL of ethanol extract for 72 h. After 48 h of treatment, LC50 values of ethanol extract and petroleum ether fraction were 956.85 and 398.73 mg/mL, respectively. After 120 h, LC50 values of the same substances were 271.23 and 152.86 mg/mL, respectively. A bioactivity-guided fractionation and chemical investigation of petroleum ether fraction yielded an active component (compound 1). NMR spectra revealed that the structure of compound 1 corresponded to 3β-hydroxy-25-methylenecycloartan-24-ol. Compound 1 also exhibited strong toxicity against the micrergates of red imported fire ants, thereby eradicating all of the tested ants treated with 240 mg/mL for 120 h. LC50 values of compound 1 at 48 and 120 h were 316.50 and 28.52 mg/mL, respectively.